2012
DOI: 10.1063/1.4772602
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a laminar-flow diffusional mixer for directed self-assembly of liposomes

Abstract: The present work describes the operation and simulation of a microfluidic laminarflow mixer. Diffusive mixing takes place between a core solution containing lipids in ethanol and a sheath solution containing aqueous buffer, leading to self assembly of liposomes. Present device architecture hydrodynamically focuses the lipid solution into a cylindrical core positioned at the center of a microfluidic channel of 125 Â 125-lm 2 cross-section. Use of the device produces liposomes in the size range of 100-300 nm, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…Later, they demonstrated controllable drug loading into the synthesized liposomes in continuous flow mode [51,54]. Kennedy et al used a 3D HF device in order to synthesize liposomes in the size range of 100–300 nm by changing sheath-to-core flow ratio, and concentrations of lipids and salts in the core and sheath flows, respectively [88]. The further study by Phapal et al showed that, in 3D HF devices, the size distribution of liposomes is strongly affected in the convective mixing regime at high Peclet number (Pe≫1) [89].…”
Section: Products Of Microfluidic Hf Based Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Later, they demonstrated controllable drug loading into the synthesized liposomes in continuous flow mode [51,54]. Kennedy et al used a 3D HF device in order to synthesize liposomes in the size range of 100–300 nm by changing sheath-to-core flow ratio, and concentrations of lipids and salts in the core and sheath flows, respectively [88]. The further study by Phapal et al showed that, in 3D HF devices, the size distribution of liposomes is strongly affected in the convective mixing regime at high Peclet number (Pe≫1) [89].…”
Section: Products Of Microfluidic Hf Based Synthesismentioning
confidence: 99%
“…(a) [88] (Printed with permission from AIP Publishing LLC) and (b) [58] (Printed with permission from IOP Publishing) shows examples of two layer on-chip 3D HF devices utilizing height variations to generate 3D-layered flow structures.…”
Section: Figmentioning
confidence: 99%
“…Mixers in microfluidics can be classified into groups of passive and active, where the second type needs an external energy supply . Forces resulting from acoustic, dielectrophoretic, electromagnetic, electrohydrodynamic, temperature gradient, and pressure perturbations are examples of external energies used to improve mixing in active mixers …”
Section: Introductionmentioning
confidence: 99%
“…Mixers in microfluidics can be classified into groups of passive and active, where the second type needs an external energy supply. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Forces resulting from acoustic, dielectrophoretic, electromagnetic, electrohydrodynamic, temperature gradient, and pressure perturbations are examples of external energies used to improve mixing in active mixers. 17 El Moctar et al 18 studied a micromixer in which two fluids with identical viscosity and density, but different electrical properties, were injected by syringe pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Exact results for advection coupled to diffusion are also known for certain geometries, notably in the case of Taylor dispersion [7]. In general, however, for predicting the steady-state distributions of particles in the presence of diffusion in arbitrary geometries, conventional strategies rely on solving the continuity equation in three dimensions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%